Taking sides : - Easton , Thomas A. (McGrawHill, 2011)
This edition of Taking sides: Clashing views on environmental issues contains 38 readings arranged in pro and con pair to form 19 issues. For each issues, an introduction provides historical background and a brief description of the debate.